The Effect of Adding Aluminum Scrap to Motor Vehicle Mufflers to Reduce the Danger of Exhaust Emissions - Ahmad Marabdi Siregar; Chandra Amirsyahputra Siregar; Khairul Umurani; Mulyadi Mulyadi; Tony Siagian; ML Teguh Samudra; Aufa Afika (Jurnal POLIMESIN, 2023)
Air pollution due to motor vehicle exhaust emissions is increased. Polluted air harms human health dan the environment. Consequently, it is essential to make a sustained effort to reduce air pollution. The purpose of this research is to investigate the effect of adding aluminum scrap to the exhaust system of a motor vehicle on gas emissions composition. The motor vehicle exhaust system was modified to accommodate aluminum scrap placement. A gas analyzer was utilized to observe exhaust gas composition, such as carbon dioxide, hydrocarbon, and carbon monoxide.  Aluminum scrap with different masses was wrapped around the exhaust's inner tube in 50 gr, 70 gr and 90 gr. The engine speed was maintained at 500 rpm throughout the testing process. It was found that the temperature of the outer exhaust tube is in a range of 40 degrees Celsius to 50 degrees Celsius. The results revealed that the most appropriate amount of aluminum scrap was 90 gr n to reduce carbon monoxide, hydrocarbon, and carbon dioxide in an exhausts gas. The surprising outcome was 76.78 % of carbon monoxide content declined, and furthermore hydrocarbon, and carbon dioxide content were deteriorated by 61.63% and 78.37%, respectively